Potential Correlation between Tumor Aggressiveness and Protein Expression Patterns of Nipple Aspirate Fluid (NAF) Revealed by Gel-Based Proteomic Analysis - Villa Flor Brunoro, Giselle; Teixeira da Silva Ferreira, Andre; Ramos de Oliveira Trugilho, Monique; Sousa de Oliveira, Tamires; Claudio Belo Amendola, Luis; Perales, Jonas; Hemmi Valente, Richard; Vitoria de Moura Gallo, Claudia; Pagnoncelli, Dante; Gisele da Costa Neves-Ferreira, Ana (Current Topics in Medicinal Chemistry, 2014)
Breast cancer is the leading cause of cancer related deaths in women. Most breast cancers stem from mammary ductal cells that secrete nipple aspirate fluid (NAF), a biological sample that contains proteins associated with the tumor microenvironment. In this study, NAF samples from both breasts of 7 Brazilian patients with unilateral breast cancer were analyzed. These samples were systematically compared using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and two-dimensional fluorescence difference gel electrophoresis (2D-DIGE); substantial qualitative individual differences were observed. In general, when NAF samples were compared from both breasts within the same patient their electrophoretic patterns were very similar, regardless of their cancer status. A comparison of all patients identified 2 main NAF protein profiles. The HomEP, homogeneous expression profile, was characterized by typical SDS-PAGE and 2D-DIGE protein patterns that were observed in patients with a good breast cancer prognosis and were similar to previous Type I NAF classifications that used one-dimensional electrophoresis. The HetEP, heterogeneous expression profile, was characterized by distinct protein patterns that have not been reported in previous studies and have been primarily observed in breast cancer patients with a poor prognosis. The NAF samples were rich in metal-dependent proteolytic enzymes, as visualized by SDS-PAGE zymography. They varied qualitatively with respect to their gelatinolytic band distribution. However, there were no correlations between these characteristics and the pathologic features of these tumors. A comparative analysis of NAF samples taken from each breast in a single patient showed conserved zymographic patterns. In conclusion, the present study highlights important distinctions in the protein content of individual NAF samples and provides insight into the composition of the tumor microenvironment. These data reinforce breast cancer as a heterogeneous disease with a diverse natural history, which is becoming increasingly evident through other recent studies.
Keywords: NAF